Assessment of emotional stress among patients suffering from obstructive sleep apnea: A cross-sectional study - Bhawna Shyamsukha; Sharayu V. Nimonkar; Vikram M. Belkhode; Priyanka Paul; Surekha Godbole (Journal of Family Medicine and Primary Care)
Background: Obstructive sleep apnea (OSA) is a sleep disorder in which the upper airway is partially or completely blocked during sleep. As a result, sleep arousal and arterial oxygen saturation are reduced. According to the epidemiological survey, OAS is relatively common among people that may be associated with psychiatric illnesses. Objectives: The primary objective was to evaluate the stress level among patients suffering from OSA. The secondary objective was to compare the gender preference for stress among patients suffering from OSA. Materials and Methods: A cross-sectional study, approved by the Institutional Ethics Committee, was performed to assess emotional stress among patients suffering from OSA. The study involved 20 participants diagnosed with OSA and reported to the Respiratory Department. The stress levels of the study participants were evaluated with a validated, Perceived Stress Scale (PSS) questionnaire given by the American Sociological Association (ASA). Result: The stress levels presented by the study participants showed that 40% (n = 8) subjects had moderate stress and 60% (n = 12) had severe stress and 30.3% of females depicted emotional stress and 26.2% of males for the same. Conclusion: There is a high psychological stress level among patients suffering from OSA. The females had higher predictions when compared to males. Such patients should be offered an intervention program aimed at stress management to enhance their quality of life.